Dialectic of Hanafiah and Istiqomah Islamic Legal Thought of Muhammad Syahrur - El karimah, Mia Fitriah (Proceeding International Conference on Religion, Science and Education, 2022)
Some Islamic thinkers argue that there is an imbalance between Islamic legal thought and solutions to modern problems. With the assumption that because of the lack of relevance to scientific tools in solving contemporary problems, the formulation of Islamic legal in the books of fiqh is experiencing a crisis of relevance, especially when it comes to contemporary themes. One of the great thinkers in the contemporary era is Muhammad Syahrur, a Syrian liberal Islamic figure. This contemporary figures tend to break away from madzhabi thinking models and use modern scientific tools, his methodologies is dismantling from etymology to morphology and redefining several important terms that have implications for new conclusions or new laws in Islamic legal. As a result, he is very contrary to the thinking of the majority of scholars. As it is known, the construction of contemporary Islamic legal in Syahrur’s perspektif is never separated from his grand theory, called as the theory of limits. He asserts that the theory of limits is an approach within ijtihad (in response to the stagnation of the study of Islamic legal thought, as well as a critique of the literal and rational groups that always dwell on the revelation and reason to provide modernity to its people). The analytical framework of Syahrûr’s limit theory arises because of the meeting of the two main characters, namely istiqâmah and hanîfiyyah, the constant form (Istiqamah) and the flexible form (hanifiyyah), these two properties are very contradictory but complementary. These two characteristics then gave birth to the limit theory. With this limit theory, Islamic law will have a dynamic movement in the midst of turmoil and the development of modern reality. This reseach used library research models, and focus on analytical descriptions from his book by qualitative model. Before raising the concepts of Syahrur’s Islamic Legal thought, tracking his methodology, approach, and technique used is an unavoidable necessity, and how does Syahrur view the existence of two main characteristics as the privilege of Islam and their relationship to Syahrur’s plausibility structure in Islamic Legal.